2022
DOI: 10.3171/2022.1.jns212724
|View full text |Cite
|
Sign up to set email alerts
|

Medication intake and hemorrhage risk in patients with familial cerebral cavernous malformations

Abstract: OBJECTIVE The objective of this study was to analyze the impact of medication intake on hemorrhage risk in patients with familial cerebral cavernous malformation (FCCM). METHODS The authors’ institutional database was screened for patients with FCCM who had been admitted to their department between 2003 and 2020. Patients with a complete magnetic resonance imaging (MRI) data set, evidence of multiple CCMs, clinical baseline characteristics, and follow-up (FU) examination were included in the study. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…41 Santos and colleagues also observed that patients on antithrombotic medication had fewer hemorrhagic events. 42 All of these studies support our findings and show that understanding the molecular signatures of coagulation in CCM could give insights regarding suitable antithrombotic pharmaceuticals for patients with CCM.…”
Section: Discussionsupporting
confidence: 86%
“…41 Santos and colleagues also observed that patients on antithrombotic medication had fewer hemorrhagic events. 42 All of these studies support our findings and show that understanding the molecular signatures of coagulation in CCM could give insights regarding suitable antithrombotic pharmaceuticals for patients with CCM.…”
Section: Discussionsupporting
confidence: 86%
“…13 16 27 Recent studies indicate that some medications can control the progression and reduce the burden of lesions in FCCM. [33][34][35][36] Thus, asymptomatic patients may benefit from FCCM drug therapy in the near future. Our study also identified ICH as the most common symptom in symptomatic patients with FCCMs.…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of hemorrhages during follow-up analysis in CCMs is a known limitation shared by other cohorts. 12,23 To overcome these limitations, prospective trials are needed, which are currently underway with the AT CASH EPOC trial, investigating the effect of atorvastatin on lesional iron deposition in CCMs. 24…”
Section: Discussionmentioning
confidence: 99%